Me MEMAHAMI CINTA, KESETIAAN, DAN HUBUNGAN MANUSIA DENGAN TUHAN DALAM KITAB KIDUNG AGUNG: Sebuah Analisis Stilistika Simbol dan Metafora - Rahmadi, Pitaya; Thiodorus, Gabriela Azelerie (Diligentia: Journal of Theology and Christian Education, 2025)
This study aims to understand the meaning of love, loyalty, and the relationship between human and God as revealed in the Book Song of Songs through a stylistic approach, especially the analysis of symbols and metaphors. The Book Song of Songs, which is rich in poetic language, is often interpreted not only as an expression of love between humans, but also as an allegory of the otherworldly relationship between humans and God. This study uses a qualitative descriptive method with text analysis techniques to identify and interpret the dominant symbols and metaphors in the text. The results of the analysis show that symbols such as gardens, grapes, flowers, and certain animals depict beauty, intimacy, and deep longing between lovers and loved ones, which in a theological context can be interpreted as a representation of the otherworldly relationship between human and God. The metaphor of love is also used to explain loyalty and pure devotion. This paper also emphasizes that the Book Song of Songs is not only a love poem but also has a deep theological meaning of a transcendental relationship. In addition, this book teaches that true love is a gift from God, and that you must live with commitment and respect. By understanding the symbols and metaphors used, readers are invited to think about the spiritual dimensions of love and loyalty in relationships between human and God.